Comparison of Post-Operative Outcomes of Intermaxillary Fixation and Open Reduction with Internal Fixation of Simple Mandibular Angle Fracture: A Randomized Control Trial (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Surgical management of simple mandibular angle fracture is a very crucial process.Objective: The purpose of the present study was to compare the post-operative outcomes of intermaxillary fixation and open reduction with internal fixation of simple mandibular angle fracture.Methodology: This randomized control trial was conducted in the Department of Oral and Maxillofacial Surgery at Dhaka Dental College & Hospital, Dhaka and Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from January 2010 to December 2010 for a period of one (01) year. Among all patients admitted/attended to the hospital IPD with fracture of mandibular angle with or without other associated fracture sites were selected as study subjects. After recruitment of the patients, they were assigned either as group A or group B after randomization. In group A the patients of this group were treated by open reduction and internal miniplate fixation with additional placement of intermaxillary fixation; in group B the patients of this group were treated by open reduction and internal miniplate fixation without any additional placement of intermaxillary fixation. During follow up period stability of fracture segments, post reduction alignment and inter-incisal opening were recorded.Result: A total of 30 patients presented with mandibular angle fractures were included in the study. They were allocated in two groups named miniplate osteosynthesis with Inter-maxillary fixation group (n=16) and without inter-maxillary fixation group (n=14) randomly. Time required to accomplish the surgical procedures was significantly high (p=0.000) group A (99.38±15.26 minutes) than group B (55.38±6.34 minutes). Among them 01 patient developed instability after inter-maxillary fixation. And 01 patient developed such in other procedure; however this difference is not statistically significant (p=0.724). In post operative radiography the mean score of post reduction alignment was slightly higher in group A than group B which was 2.50±0.516 and 2.214±0.426 respectively (p=0.107). The inter-incisal opening in baseline was 14.69 and 18.14 in group A and group B respectively. However, in review 3 it was found 36.19 and 37.64 in group A and group B respectively (p=0.0001).Conclusion: In conclusion significantly less operative time was required to accomplish the operative procedure in without IMF group as well as there was also a significant difference of inter-incisal opening between two procedures in subsequent review findingsJournal of National Institute of Neurosciences Bangladesh, 2018;4(2): 108-112